Decriminalising Abortion in the UK What Would It Mean? - Sheldon, Sally; Wellings , Kaye (2019)
"Available Open Access under CC-BY-NC licence. The public and parliamentary debate about UK abortion law is often diverted away from key moral and political questions by disputes regarding basic questions of fact. And all too often, claims of scientific 'fact' are ideologically driven. With each chapter written by leading experts in the fields of medicine, law, reproductive health and social science, this book offers a concise and authoritative account of the evidence regarding the likely impact of decriminalisation. Examining specific yet diverse regional and local contexts across Europe, this book uses original research to evaluate differences in scope, approach, orientation, and objectives. It examines the embedding of LLL policies into the regional economy, the labour market, education and training systems and the individual life projects of young people, with a focus on those in situations of near social exclusion. "